(untitled) (Superficies y Vacío, 2012)
Photothermal techniques have been used to characterize the thermal and optical parameters of different homogeneous materials. Among these techniques the photopyroelectric and photoacoustic microscopy have been applied for obtaining superficial and in-depth thermal images of several materials with the possibility to obtain sub-superficial characteristics by changing the modulation frequency of the incident light on the sample under study. In the present research the thermal image of a non-homogeneous material such as a biological object, in this case a maize seed was obtained by photopyroelectric microscopy. The differences in the seed structural components were observed through its thermal image obtained from the photopyroelectric signal when the modulated light is scanned on the pyroelectric sensor, which is in good thermal contact with the sample. A scale of colors is used to represent the different values of the photopyroelectric signal, as a function of the scan coordinates, which allows observing better the seed components. The differences of photopyroelectric signal are caused by the inhomogeneities in the optical and thermal properties of the material which locally constituting the sample. In the case of this study the sample was an infected seed with “Palomilla” (Ostrinia nubilalis) plague and the thermal image shows the damage at the interior of the maize seed due to this plague.